Comparative histomorphological study of non affected and affected liver by fascioliasis in Black Bengal goat - Islam, Md Reazul; Parvez, Md Najmul Hassan; Sarder, Md Jalal Uddin (Asian Journal of Medical and Biological Research, 2016)
The purpose of this study was to comparative histomorphological investigation of the non affected and affected liver by fascioliasis in Black Bengal goat. The average weight of affected livers was 511.20±14.10 gm which was significantly (p<0.001) higher than non affected livers (371.70±13.25 gm). The average length and girth of affected liver were 27.50 ±0.63 cm and 34.00±0.71 cm, respectively which were also significantly (p<0.001) higher than the length (21.80±0.61 cm) and girth (26.60±0.80 cm) of non affected liver of Black Bengal goat. The gross changes in acute form, affected livers were enlarged than normal. The livers were slightly swollen with rounded edges and the color became paler than normal. The capsule was more or less thick, opaque and rough than normal smooth thin capsule. The gross changes of the liver in chronic fascioliasis characterized by increase in the size of the organ due to inflammatory changes in the parenchyma and fibrosis of the bile ducts containing adult flukes. In acute cases microscopic changes were found mainly in the portal area. The grossly visible spots or tracks was represented by the presence of numerous eosinophils admixed with few lymphocytes and monocytes in the parenchyma of liver and accompanied by hemorrhage and edema. In chronic fascioliasis the hemorrhagic tracks or tunnels were represented by the areas infiltrated with fibroblasts admixed with neutrophils, lymphocytes and few mononuclear cells in the area previously migrated by young flukes. So it was concluded that liver of Black Bengal goats are mostly affected with fascioliasis which severely change the structure of that organ. Asian J. Med. Biol. Res. December 2015, 1(3): 424-433